Classifying Optical (Out)bursts in Cataclysmic Variables: The Distinct Observational Characteristics of Dwarf Novae, Micronovae, Stellar Flares, and Magnetic Gating - Krystian Iłkiewicz; Simone Scaringi; Martina Veresvarska; Domitilla De Martino; Colin Littlefield; Christian Knigge; John A. Paice; Anwesha Sahu (The Astrophysical Journal Letters, 2024)
Cataclysmic variables can experience short optical brightenings, which are commonly attributed to phenomena such as dwarf novae outbursts, micronovae, donor flares, or magnetic gating bursts. Since these events exhibit similar observational characteristics, their identification has often been ambiguous. In particular, magnetic gating bursts and micronovae have been suggested as alternative interpretations of the same phenomena. Here we show that the timescales and energies separate the optical brightenings into separate clusters consistent with their different classifications. This suggests that micronovae and magnetic gating bursts are in fact separate phenomena. Based on our findings, we develop diagnostic diagrams that can distinguish between these bursts/flares based on their properties. We demonstrate the effectiveness of this approach on observations of a newly identified intermediate polar, CTCV J0333-4451, which we classify as a magnetic gating system. CTCV J0333-4451 is the third highest spin-to-orbital period ratio intermediate polar with magnetic gating, suggesting that these bursts are common among these rare systems.